EFFECT OF AGE, DOUBLE PREGNANCY, AND GRAVIDA ON THE PREECLAMPSIA IN THE GENERAL HOSPITAL OF MEURAXA BANDA ACEH IN 2014 - A, Raudhatun Nuzul Z; Priani, Pipit (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2017)
Preeclampsia has an impact on renal function. Preeclampsia may also be made more complicated by the presence of convulsions called eclampsia and resulted in many maternal deaths associated with hypertension, preeclampsia and eclampsia patients in the Meuraxa public hospital midwifery room in 2014 recorded 491 who gave birth to preeclamps cases of 30 and In the year 2015 recorded sebayak 560 people who gave birth with preeklamsi cases as many as 30 people, from this data there is an increase in 2015 as many as 69 people give birth. Research purpose: To know the effect of age, multiple pregnancy, and gravida on the incidence of preeclampsia at Meuraxa General Hospital at Banda Aceh 2014. This research is an analytical survey with Case Control design. The population in this study were all mothers who gave birth at the Meuraxa general hospital. The sample of this study were 40 people consisting of 20 cases and 20 controls. This research was conducted on 31 May to 7 June 2016. Data collection was done by using research form using secondary data. Then in the statistic using chi-quare, Ho is rejected if p- value> 0.05 and Ha is accepted if p- value <0.05. The results showed that based on the results of statistic obtained p-value = 0.001 means there is influence between maternal age with the incidence of preeclampsia and the results of OR 21,000. While the result of tesistatistik obtained p-value = 0.068 means there is no influence between multiple pregnancy with the incidence of preeclampsia and the value of OR 6,000. Then the results obtained tahistatistik p-value = 0.001 means there is the influence of gravida with the incidence of preeclampsia and OR value of 0.076. There is an influence of maternal age, no multiple pregnancy effects, there is a gravida effect with preeclampsia occurrence. For it is expected to pregnant women and maternity mothers to do prevention so as not to experience preeklamsi events and can provide new imformasi for educational institutions and for the next author who want to do the other research.Keywords: age, double pregnancy, and gravida on the preeclampsiaÂ